Propuesta de diseño del Sistema de Gestión de Seguridad y Salud en el Trabajo mediante la Resolución 0312 de 2019 para la empresa El Viñedo (2022)
A design proposal for the Occupational Health and Safety Management System was proposed for the company El Viñedo, based on resolution 0312 of 2019, which contains a series of steps that companies must comply with, according to their size and level of risk., in order to generate a clearer orientation to the organization of the importance of SG-SST, in the work environment. Based on what was found in the initial diagnosis, it was possible to show that the company at the moment does not meet any requirement requested by the resolution, that is why a step by step is carried out with proposals based on real information from which the company It can be based for its possible implementation, related to the risks and dangers identified according to the tasks and organizational environment.